The authority of public policy and its applications in financial transactions - Zairi, Muhammad Zarul Iman; Muhd Rafi, Muhammad Jamaluddin; Mohd Adanan, Muhammad Haris Iqbal; Zulkefli, Muhammad Hamiz; Ahmad Jailani, Alif Ramdhan Naimullah (2024)
Istihsan is one of the important methods in fundamental jurisprudence used by scholars to resolve complex legal issues that cannot be resolved through ordinary methods such as analogy or general evidence. This method plays a role in providing flexibility to Islamic law, especially in ensuring its suitability to the current situation and not burdening Muslims. Istihsan tends to choose a better legal settlement based on benefit and justice, as long as it does not conflict with the principles of Sharia. In the context of the development of Islamic law, istihsan emerged as one of the methods of ijtihad that complemented other methods such as analogy, consensus, and reform. Scholars recognize that there are cases in which the use of general evidence or analogy can lead to discomfort (haraj) or injustice. Therefore, istihsan is applied to provide a more appropriate solution while taking into account the tawj. In the context of the development of Islamic law, istihsan emerged as one of the methods of ijtihad that worked to complement other methods such as analogy, consensus, and reform. Scholars recognize that there are cases in which the use of general evidence or analogy can lead to inconvenience (haraj) or injustice. Therefore, istihsan is applied to provide a more appropriate solution, taking into account the purpose of the Sharia (maqasid al-sharia) and the needs of society. Among the objectives are to resolve conflicts between general principles and certain circumstances that require exceptions, to ensure that the rulings issued are in line with the interests of the nation and relevant to the current reality, to avoid difficulties, and to ensure adherence to the principle of justice in all aspects of life, including matters of transactions.